Change : how organizations achieve hard-to-imagine results in uncertain and volatile times - Kotter, John P., 1947-; Akhtar, Vanessa; Gupta, Gaurav (Strategy and Change Execution Professional) (2021)
"The ability of organizations to deal with threats and take advantage of opportunities in the face of ever greater complexity and uncertainty is being severely challenged. Over the last century, increasing sophistication of management tools and change methodologies has provided much incremental improvement in enterprise capacity to adapt and adjust. However, incremental is no longer sufficient. We need a new way to drive change in organizations, and this book will reveal just that. The authors build upon an emerging science to show how businesses and governments can dramatically improve their results from strategy execution, digital transformation, restructuring, and more. These insights, and the approach described, are universally applicable to leading organizational change in our more volatile and unpredictable world. There is no published material that addresses today's real change challenge for organizations and presents an evidence-based solution, and there is no other accessible and actionable book based on a larger or more in depth research program. In this book, the authors demonstrate that there is an emerging science of change that can teach us much about how to build organizations that are more agile and able to change rapidly. At Kotter International, the authors have seen some organizations and leaders apply lessons from this science to take a very different path than the norm. They will describe these success stories and contrast them to others that failed to have the same impact."--
Includes index.
Keywords: Organizational change; Organizational change; Electronic books